Antigenic reactivity of peptides derived from wheat gluten with sera from patients with coeliac disease. - Rawcliffe, P; Priddle, J; Jewell, D (1985)
Fraction B from a peptic-tryptic digest of gluten from Scout 66 wheat has already been shown to cause histological damage to the jejunal mucosa of coeliac patients. Peptide fractions, designated P1-P4, have been prepared from it by a combination of gel filtration (producing an intermediate fraction pseudo-B2: psi B2) and reverse-phase high pressure liquid chromatography. An enzyme-linked immunosorbent assay (ELISA) has been used to measure IgG antibodies to fraction B in sera from untreated coeliac patients, patients with inflammatory bowel disease (IBD) and healthy individuals. The coeliac group had significantly higher (P less than 0.05) antibody levels to fraction B than either of the control groups [medians: coeliac disease (n = 21), 0.247; IBD (n = 17) 0.019; healthy controls (n = 13) 0.020]. Five coeliac sera which gave high absorbance values in the ELISA were chosen and preincubated with fraction B in a range of concentrations, before assay by ELISA: a dose-dependent inhibition of binding was found. Two sera which gave high ELISA values were preincubated with fractions B2 and P1-P4. B2, P1, P2 and P4 gave a dose-dependent inhibition, with P1 being the most potent. Absolute values were different for the two sera but the same relative pattern of reactivity was observed for each. With the serum giving the higher ELISA value the concentration of fraction (microgram/ml) giving a 50% inhibition of binding when 0.5 ml was added to 0.5 ml of a 1/500 dilution of the serum (IC50) was 2.6 for fraction B, 61 for P1, 155 for B2 and 285 and 295 for P4 and P2 respectively.(ABSTRACT TRUNCATED AT 250 WORDS)